(untitled) (Gaceta de Ciencias Veterinarias, 2017)
Among the antibiotics that can cause fatty liver (HG) is oxytetracycline (OT). This study aimed to determine the hepatic damage of a high dose of OT in pregnant female mice and its association with oxidative stress (OE). 30 NMRI female mice distributed in three groups of 10 animals: Day 0 not pregnant, to Parturition, maintained until delivery, to Weaning, maintained until weaning. In all, half was injected i.p. with a single dose of 100 mg/kg OT, experimental group. The results are the mean±SE, the statistical significance was obtained by Student´s t-test. HG was evaluated by histology and by the concentration of hepatic triglycerides. As OE parameters, the hepatic concentration of conjugated dienes (DC) and MDA was determined by spectrophotometry. Liver function was assessed by the plasma activity of the aminotransferases ALT and AST by commercial kits. The results showed that a high dose of OT, at 24 hours in non-pregnant female mice (Day 0 group) elevated the hepatic triglycerides, accompanied by hepatoesteatosis and increased plasma ALT and AST. OE was found in them, evidenced by high concentration of DC and MDA. At delivery, the experimental pregnant females did not present any modification of the parameters described in the Day 0 group, evidencing that at 21 days after the administration of a high OT dose, the effect of the anibiotic was not maintained, a similar result was obtained in the females at the time of weaning.